NIGERIAN PALM OIL: QUALITY DISPARITY, CONTAMINATION AND PROCESSING WASTES HANDLING - Abdullahi, N.; Umar, N. B.; Tsoho, A. U.; Sani, A.; Yazeed, Z. M.; Tsangaya, M. A.; Yahaya, Y. A.; Yusuf, K.; Haruna, S. A.; Abdullahi, U. A.; Ali, A.; Dahiru, U. M.; et al. (FUDMA JOURNAL OF SCIENCES, 2023)
The review article intended to provide an overview of quality variation and various contaminants in locally processed palm oil (PO). The paper also deliberates on the pros and cons of wastes generated during PO processing. There is a serious concern about the quality and safety of crude PO in Nigeria resulting from poor quality raw materials, inadequate processing know-how, inappropriate packaging and storage facilities, poor handling and transportation system and more importantly adulteration by producers and marketers. Wide disparities in the chemical and physical composition were reported in the literature. This may result from the variations in the chemical composition of the palm fruit, environmental factors, variation in processing operations which is determined by the location and abuse during handling and transportation. Microbial contamination is the foremost safety challenge in Nigerian crude PO processing. Higher microbial counts and the presence of toxic microorganisms including aflatoxins-producing fungi were reported by many researchers. Oil palm production in contaminated soil account for PO heavy metals contamination, though, heavy metals contamination below permissible limits was reported in most cases. Wastes generated from PO processing can be detrimental to the environment. Alternately, various benefits can be derived from the proper handling and utilisation of PO processing wastes. Palm oil mill effluent (POME) is a good substrate for the production of organic manure, biomolecules and amendment of oil-contaminated soil. Recommendations on how to tackle various challenges along the PO supply chain were presented at the end of the paper.